Implications of consumer-oriented food subsidies for domestic agriculture - von Braun, Joachim (International Food Policy Research Institute, 1988)
This chapter does not attempt to provide a balanced assessment of the costs and benefits of food subsidy systems. Rather, it focuses on answering three questions: 1. What are the mechanisms through which consumer-oriented food subsidies affect domestic agriculture? 2. To what extent do consumer-oriented food subsidies burden domestic agriculture? That is, what is the empirical evidence? 3. How may the potentially negative effects of consumer-oriented food subsidies on domestic agriculture be avoided?